Mechanical activation and physical properties of Pb(Zr0.56Ti0.44)O3. (4th April 2018) - Sirota, M. A.; Abdulvakhidov, K. G.; Budnyk, A. P.; Soldatov, A. V.; Bugaev, A. L.; Lastovina, T. A.; Kabirov, Yu. V.; Mazuritskiy, M. I.; Plyaka, P. S.; Kallaev, S. N.; Omarov, Z. M.; Sadykov, S. A.; et al.
ABSTRACT: The Pb(Zr0.56 Ti0.44 )O3 (PZT) ceramics was subjected to a pressure-induced activation at 320 MPa in a Bridgman anvil, where a load pressure was combined with a shear deformation. The induced changes in the linear and angular parameters of a unit cell, in the ratio of coexisting rhombohedral ( R3m ) and tetragonal ( P4mm ) phases as well as in the dielectric properties were analyzed.